2002
DOI: 10.1557/jmr.2002.0231
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Prototyping of Micropatterned Substrates Using Conventional Laser Printers

Abstract: We demonstrated rapid prototyping of templates for replica molding using a conventional laser printer. A polymer, polydimethylsiloxane, was cast directly on the transparency templates to make the replicas. The templates and replicas were characterized by scanning electron microscopy, profilometry, and optical microscopy. Four patterns, including an Electronic Industries Association resolution test pattern, were printed on transparencies at 600 dots per inch on a HP LaserJet 4M printer (Hewlett-Packard, Palo Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…In 2002, Shyy et al 11. reported replication of positive-relief patterns printed with an office LaserJet printer.…”
Section: Development Of Papmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2002, Shyy et al 11. reported replication of positive-relief patterns printed with an office LaserJet printer.…”
Section: Development Of Papmentioning
confidence: 99%
“…The patterns were printed on overhead transparencies, over which PDMS was cast. The reproduction of patterns of lines with different widths was tested 11. Several years later, Chen et al 6.…”
Section: Development Of Papmentioning
confidence: 99%
See 1 more Smart Citation
“…The versatility of the direct-printing process allows it to produce masters or molds for rapid prototyping of polymeric devices. Two different groups [32,33] demonstrated that the printing of a toner layer on the transparency could be used as the positive relief of the masters. Examples of PDMS electrophoresis devices were successfully obtained and integrated to electrochemical detection of electroactive biological molecules and nonelectroactive inorganic ions [33].…”
Section: Masters For Soft Lithographymentioning
confidence: 99%
“…Two types of office-grade printers have been used for the PAP method: laser printer [2][3][4][5] and solid-ink printer [6][7][8]. Although laser printers can produce microfluidic molds based on the PAP method, solid-ink printers have an advantage that their solid ink can be printed on nearly any media [9].…”
Section: Introductionmentioning
confidence: 99%